Unpacking Human Trafficking from Neoliberalism and Neoconservatism Paradigms in Nepal: A Critical Review - Dhungel, Rita (Molung Educational Frontier, 2021)
This theoretical review paper examines the trafficking of women and children in Nepal caused by oppression and socio-economic marginalization and unpacks human trafficking from neoliberal and neoconservative paradigms. It does not discuss human smuggling but instead provides a critical examination of the forces contributing to human trafficking in Nepal according to the neoliberal and neoconservative paradigms. It begins with a brief overview of human trafficking in Nepal and then explores the international frameworks related to human traﬃcking. It then briefly examines the “4 P” strategy – prevention, protection, prosecution and partnerships – related to anti-human trafficking efforts and identifies gaps in practice/policies. It concludes with a critical discussion of the implications for social work. The paper also stresses that anti-trafficking intervention programs and approaches must be accountable and responsive to the aspirations, strengths, wisdom and experiences of the speciﬁc community and be sensitive to the external and internal forces contributing to the trafficking they seek counter. It claims that there is a need for participatory action research that invites trafficking survivors to engage in critical dialogue and conversation and help develop integrative strategies to address human trafficking in Nepal. To write this paper, the author critically reviewed secondary data, including qualitative and quantitative studies and NGO publications, but does not claim to provide a comprehensive or systematic analysis of evidence.